2012
DOI: 10.3109/14767058.2012.700344
|View full text |Cite
|
Sign up to set email alerts
|

Can third trimester ultrasound predict the presentation of the first twin at delivery?

Abstract: The presentation of the first twin at delivery can be determined by sonogram by the 32nd week of gestation in over 90% of twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Our main findings are as follows: 1) twin A tends to remain stable in the vertex presentation after 32 weeks of gestation with a likelihood of spontaneous version to nonvertex presentation of only approximately 3%; 2) the presentation of twin B is less stable and changes in approximately 25% of cases-this remains true even when twin B is in the vertex presentation (version rate of 17%) and even late in the third trimester (version rate of higher than 20% after 34 weeks of gestation); 3) both twins are more likely to change their presentation when twin B is in the nonvertex presentation and is smaller, and as the interval to delivery after the ultrasound examination increases; 4) twin A is also more likely to switch to nonvertex presentation when twin B changes its presentation; and 5) the presentation of twin B is less stable in multiparous women. Information regarding the likelihood of spontaneous version of twins during the third trimester has been addressed previously by only a small number of studies, [8][9][10][11] which were limited by relatively small sample sizes (n5119-491) and by limiting the analysis only to the presenting twin. 10 We have found that twin A tends to remain stable after 32 weeks of gestation and that the vertex-vertex presentation is the most stable combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our main findings are as follows: 1) twin A tends to remain stable in the vertex presentation after 32 weeks of gestation with a likelihood of spontaneous version to nonvertex presentation of only approximately 3%; 2) the presentation of twin B is less stable and changes in approximately 25% of cases-this remains true even when twin B is in the vertex presentation (version rate of 17%) and even late in the third trimester (version rate of higher than 20% after 34 weeks of gestation); 3) both twins are more likely to change their presentation when twin B is in the nonvertex presentation and is smaller, and as the interval to delivery after the ultrasound examination increases; 4) twin A is also more likely to switch to nonvertex presentation when twin B changes its presentation; and 5) the presentation of twin B is less stable in multiparous women. Information regarding the likelihood of spontaneous version of twins during the third trimester has been addressed previously by only a small number of studies, [8][9][10][11] which were limited by relatively small sample sizes (n5119-491) and by limiting the analysis only to the presenting twin. 10 We have found that twin A tends to remain stable after 32 weeks of gestation and that the vertex-vertex presentation is the most stable combination.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the likelihood of spontaneous version of twins during the third trimester has been addressed previously by only a small number of studies, [8][9][10][11] which were limited by relatively small sample sizes (n5119-491) and by limiting the analysis only to the presenting twin. 10 We have found that twin A tends to remain stable after 32 weeks of gestation and that the vertex-vertex presentation is the most stable combination. These findings are in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with our data, Chasen et al (2005) and Divon et al (1993) also reported that vertex presentation was most stable in twin gestations. In vertex-presenting first twins after 28 or 32 weeks of gestation, ultrasound can predict the first twin presentation at birth in 90% and 95% or more of cases respectively (Chasen et al, 2005; Divon et al, 1993; Fox et al, 2013; Melamed et al, 2015; Schwartz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported on the spontaneous version in twin gestations, their methods had one or more limitations, and their results were limited due to small sample sizes, inappropriate timing of enrollment, limited study population originating from secondary analysis of a previous large study, or cross-sectional analysis between only two time intervals (Chasen et al, 2005; Divon et al, 1993; Fox et al, 2013; Melamed et al, 2015; Santolaya et al, 1992; Schwartz et al, 2012). In 2015, Melamed et al reported the secondary analysis of a previous large randomized controlled trial on the mode of delivery in twin pregnancies.…”
Section: Discussionmentioning
confidence: 99%